2004
DOI: 10.2514/1.3165
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Modeling and System Identification from Flight Data-Recent Applications at DLR

Abstract: This paper provides an overview of a few selected system-identification activities carried out during the last decade at DLR, the German Aerospace Center. After a brief account of parameter-estimation methods and of consistency checking of recorded flight data, an emphasis is placed on 1) development of global, high-fidelity aerodynamic databases for training simulators; 2) models for in-flight simulator; 3) modeling of stall hysteresis; 4) estimation of aerodynamic flowfield characteristics and validation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 29 publications
0
98
0
Order By: Relevance
“…This method was deemed feasible by Barrows [34], verified against wind-tunnel tests by de Bruin [35], and further validated using flight-test data by Fischenberg [36] and Jategaonkar et al [37].…”
Section: B Implementation Of Vortex Flowfields In the Aircraft Simulmentioning
confidence: 90%
“…This method was deemed feasible by Barrows [34], verified against wind-tunnel tests by de Bruin [35], and further validated using flight-test data by Fischenberg [36] and Jategaonkar et al [37].…”
Section: B Implementation Of Vortex Flowfields In the Aircraft Simulmentioning
confidence: 90%
“…SID is usually applied to wind tunnel and flight test data to obtain accurate and comprehensive mathematical models of aircraft aerodynamics, for aircraft flight simulation, control system design and evaluation, and dynamic analysis. A very comprehensive review of SID applied to aircraft can be found in Morelli and Klein [9,10] and Jategaonkar [11,12] . Aircraft system identification can be used in cooperative approaches with CFD, to take advantage of the strength of both approaches or having one approach fill in the gaps where the other cannot be used effectively [9] .…”
Section: System Identification Analysis (Sidpac)mentioning
confidence: 99%
“…In system theory, this process is known as system identification and the objective is to obtain dynamic models from observed input and output signals [3]. In particular, system identification methods have been used for flight-test evaluations [4][5][6][7][8][9][10], control analysis and design [11,12] and advanced simulation [13][14][15].…”
Section: Introductionmentioning
confidence: 99%